Strategi Efektif untuk Meningkatkan Pemahaman Nahwu dalam Pembelajaran Bahasa Arab - Ghoffar, Achmad Mujahid; Muid , Faruq Abdul (Journal of Practice Learning and Educational Development, 2024)
This article explores effective strategies for improving the understanding of nahwu in Arabic language learning, given the complexity of the nahwu rules that are often challenging for students. Using a qualitative approach to case study design, the study involves observations, interviews, and document analysis to evaluate various methods of teaching nahwu. The results show that contextual approaches, interactive media, collaborative learning, and problem-based approaches significantly improve student understanding of Nahwu. This article recommends the implementation of these strategies in the Arabic curriculum in schools and suggests further research to explore the application of this strategy in the context of other Nahwu learning and different Arabic language skills.